EVALUASI PADA WEBSITE SRAGENKAB.GO.ID MENGGUNAKAN METODE WEB USABILITY EVALUATION (WEBUSE) DAN WEB CONTENT ACCESSIBILITY GUIDELINES (WCAG) 2.1 - Siti Fatimah; Ahmad Hanafi; Kharisma; Alfun Roehatul Jannah (Jurnal Teknomatika, 2023)
The sragenkab.go.id website serves as a vital platform supporting the operations of the Sragen district government, disseminating accurate and prompt information to the public. However, various issues hamper its functionality, such as interface display problems, unclear layout, non-functional links, excessively simple design, and slow response times. To address these concerns, this study aims to evaluate the sragenkab.go.id website's usability and accessibility aspects using the Website Usability Evaluation (WEBUSE) method and the Web Content Accessibility Guideline (WCAG) 2.1 method, respectively. Using the WEBUSE method, a survey questionnaire was distributed to 100 respondents from Sragen to assess the usability level of the website. The obtained score of 0.65 indicated that the website's usability is categorized as "good" and has been accepted by the users. On the other hand, the accessibility evaluation using the WCAG 2.1 method, with the assistance of the WAVE tool and accessibilitychecker, revealed a score below 75%, indicating a significant risk of non-compliance with international accessibility standards. In conclusion, the sragenkab.go.id website exhibits commendable usability; however, it falls short in terms of accessibility. The findings emphasize the importance of optimizing the website's accessibility to adhere to international regulatory standards, ensuring equitable access to information and services for all users. Future improvement efforts should focus on rectifying accessibility issues to enhance the overall user experience and inclusivity of the website.